Expression of the chicken GDNF family receptor α-1 as a marker of spermatogonial stem cells - Mucksová, J; Kalina, J; Bakst, M; Yan, H; Brillard, J P; Benešová, B; Fafílek, B; Hejnar, J; Trefil, P (Animal reproduction science, 2013)
The identification, enrichment and subsequent isolation of spermatogonial stem cells (SSCs) are integral to the success of SCC transplants between fertile donor and sterilized recipient males. In birds generally and particularly in chicken, SSC-specific has yet to be identified. The receptor for glial cell-derived neurotrophic factor (GDNF), i.e. GDNF family receptor alpha-1 (GFRα1), has been identified as a potential marker for different mouse spermatogonial subtypes. In the present study, we characterized the chicken cGFRα1 receptor and compared its predicted amino-acid sequence with mouse, rat and human GFRα1 proteins. Using specific polyclonal mouse anti-cGFRα1 serum, a total of 2.8% cells were recognized as cGFRα1-positive among isolated testicular cells recovered from sexually mature cockerels. The percentages of cGFRα1-positive testicular cells with haploid, diploid, tetraploid and SP DNA content were 1.6%, 2.5%, 39.3% and 76.8%, respectively. The presence of cGFRα1 protein on the surfaces of all cells of the seminiferous epithelium was confirmed by immunocytochemical and immunohistochemical analyses. Tissue specificity of cGFRα1 mRNA expression was significantly higher in adult testes compared to brain tissue which itself was several times higher than tissues prepared from the spleen, liver and heart. No expression was observed in muscular tissue. At last, we demonstrated the successful repopulation of sterilized recipient's testes with transplanted cGFRα1-positive donor testicular cells. Recipient males subsequently produced functional heterologous spermatozoa capable of fertilizing an ovum and obtaining chicks with donor cell genotypes.
Keywords: Molecular Sequence Data; receptory GDNF; sekvence aminokyselin; transplantace kmenových buněk; Real-Time Polymerase Chain Reaction; genotyp; Antibodies; protilátky; Genotype; Glial Cell Line-Derived Neurotrophic Factor Receptors; Gene Expression Regulation; mužské pohlaví; testis; Adult Stem Cells; Cloning, Molecular; kvantitativní polymerázová řetězová reakce; regulace genové exprese; zvířata; dospělé kmenové buňky; Amino Acid Sequence; biologické markery; Stem Cell Transplantation; klonování DNA; molekulární sekvence - údaje; Biomarkers; GFRα1; Male germ line transplantation; Testis; Chicken spermatogonial stem cell; Male; Animals